Evaluation of antioxidant activity and cytotoxic potential of Cryp-tocoryne ciliata - Nahar, Ummey Jannatun; Lina, Shah Marzia Mahjabin (International Current Pharmaceutical Journal, 2013)
Cryptocoryne ciliata belonging to the Araceae family has been investigated for isolation of its secondary metabolites and evaluation of biological activities of the crude extractives with special emphasis to the antioxidant activity and brine shrimp lethality bioassay. The whole plant was extracted with methanol and concentrated extract was partitioned using petroleum ether, carbon tetrachloride and ethyl acetate. Aqueous soluble fraction of the methanolic extract showed the highest antioxidant activity. The carbon tetrachloride soluble fraction of the methanolic extract and the ethyl acetate soluble fraction of the methanolic extract showed moderate antioxidant activity as compared to free antioxidant activity of tert-butyl-1-hydroxytolunene. In the brine shrimp lethality bioassay, among all extracts of whole plant of C. ciliata, the carbon tetrachloride soluble fraction of the methanolic extract showed strong cytotoxic activity. Aqueous soluble fraction of the methanolic extract, methanolic crude and ethyl acetate soluble fraction of the methanolic extract showed mild cytotoxity as compared to that of vincristine sulphate. The study confirms the mild to moderate antioxidant and moderate potent cytotoxic activities of C. ciliata plant extract as compared to reference standards and therefore demands the isolation of active principles and thorough bioassay. DOI: http://dx.doi.org/10.3329/icpj.v2i2.13196 International Current Pharmaceutical Journal 2013, 2(2): 38-41